2014
DOI: 10.1186/1471-2229-14-163
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of proteins related to rice grain chalkiness using iTRAQ and a novel comparison system based on a notched-belly mutant with white-belly

Abstract: BackgroundGrain chalkiness is a complex trait adversely affecting appearance and milling quality, and therefore has been one of principal targets for rice improvement. Eliminating chalkiness from rice has been a daunting task due to the complex interaction between genotype and environment and the lack of molecular markers. In addition, the molecular mechanisms underlying grain chalkiness formation are still imperfectly understood.ResultsWe identified a notched-belly mutant (DY1102) with high percentage of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 36 publications
3
72
0
Order By: Relevance
“…Substantial advances in elucidating the mechanisms governing chalkiness formation have been made, as evidenced by the cloning of controlling genes like Chalk5 , and the comprehensive analysis of related enzymes and their regulatory pathways by the tools of proteomics and transcriptomics . However, the molecular and biochemical mechanisms underlying chalkiness formation are still imperfectly understood, owing to the complex interaction between genotype and environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial advances in elucidating the mechanisms governing chalkiness formation have been made, as evidenced by the cloning of controlling genes like Chalk5 , and the comprehensive analysis of related enzymes and their regulatory pathways by the tools of proteomics and transcriptomics . However, the molecular and biochemical mechanisms underlying chalkiness formation are still imperfectly understood, owing to the complex interaction between genotype and environment.…”
Section: Discussionmentioning
confidence: 99%
“…A notched‐belly mutant (DY1102) with high occurrence of white‐belly grains was used in this study. Identification and characterization of the mutant were presented in detail in our previous report . Briefly, the mutant has a high percentage of notched‐belly grain (83%), of which 85% had white‐belly that occurs only in the bottom part proximal to the embryo (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was supported by the greater abundance of PRO7, a seed storage protein and GRXC8 (glutaredoxin‐C8), an enzyme that scavenges reactive oxygen species (Lin et al ., ). In rice, prolamins accumulate in the PB‐I compartments which bud directly from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, accumulations of prolamin and globulin, but not of glutelin and albumin, are reduced under high temperatures (Yamakawa et al 2007;Lin et al 2010). Enhanced expression of small heat shock proteins or redox homeostasis-related genes under high temperatures is strongly correlated with the occurrence of chalky grains, as demonstrated in studies of various conventional cultivars and transgenic lines of rice (Lin et al 2005(Lin et al , 2014Liu et al 2010Liu et al , 2011. Metabolomic analysis of the developing caryopsis has indicated that high temperatures decrease the levels of glucose, fructose, most sugar phosphates, and organic acids involved in glycolysis/gluconeogenesis and the TCA cycle while increasing the amounts of sucrose, UDP-glucose, and ADP-glucose (Yamakawa and Hakata 2010).…”
Section: Newly Identified Rice Genes For Heat-stress Tolerance That Amentioning
confidence: 90%